Racial and prejudicial stereotyping by police : its impact on investigative interviewing and the outcomes of criminal investigations - Minhas, Rashid (Criminologist) (New York, NY : Routledge, 2024)
"This book uncovers the influence of racial and prejudicial stereotyping during police investigation of suspects from stigmatised communities. The book examines the under-researched aspect of whether and how negative stereotypes appear to influence the police interviews, investigative decision-making, and outcomes of criminal investigations when officers investigate individuals from stigmatised communities as suspects of crime. In the UK, the US, and Europe, the war on terror has been argued to impact adversely on existing race relations policies. In the aftermath of terrorist activity in both the US and Europe. Recent research has suggested that changes in legislation and counter-terrorism measures have contributed to the construction and reinforcement of the Muslim community as a suspect, which, in turn, may result in police bias and prejudice towards members of the Muslim communities. Based on novel and groundbreaking research studies, the author examines whether such police bias could influence the police investigation and interviewing processes concerning individuals from the suspect community as well as the outcome of a criminal investigation. The author introduces the Minhas Investigative Interviewing Prejudicial Stereotyping Scale (MIIPSS), an instrument developed and used to assess the level of police interviewers' racial and prejudicial stereotyping towards suspects from stigmatised groups, and maintains that its use would serve to minimise the influence of racial and prejudicial stereotypes on investigation. It is further suggested that training of police officers on the implications of such prejudicial (racial/religious) stereotyping is essential to improving interviewing performance, case outcomes, and community cohesion. This book will benefit academics, researchers, police officers, lawyers, social policy officers, and probation officers across the globe"--
Keywords: Racial profiling in law enforcement; Racism in law enforcement; Stereotypes (Social psychology); LAW / Forensic Science; SOCIAL SCIENCE / Criminology